Consolidation of human movement science as a STEM discipline - Rojas-Valverde, Daniel (2026)
The recognition of Human Movement Science (HMS) as a STEM (Science, Technology, Engineering and Mathematics) discipline involves a strategic step towards the scientific and technological consolidation of HMS professionals in Costa Rica. This article examines the curricular, methodological and epistemological structures of HMS to validate its alignment with the STEM criteria set forth by international organizations such as UNESCO. On the basis of a study of Costa Rican university programs and international references, the article proves that HMS includes foundations of biology, physics, mathematics and applied engineering, using advanced technological tools, data analysis and the analysis of complex biological systems. Likewise, the concept of “human body engineering” is proposed as the articulation of the four STEM axes in HMS. Future actions are proposed for strengthening its formal recognition, curricular harmonization, the promotion of interdisciplinary research, technological development, teacher training and political university management. Not regarding HMS as a STEM discipline would involve perpetuating a reductionist view that ignores the role of this discipline as a bridge between science, technology, data analysis, sports and health. Finally, it is concluded that HMS integrates a model of interdisciplinary applied science with a high potential for driving innovation, scientific literacy and the sustainability of knowledge in health and sports.